Environmental science and information application technology : proceedings of the 2014 5th International Conference on Environmental Science and Information Application Technology (ESIAT 2014), November 7-8, 2014, Hong Kong /: proceedings of the 2014 5th International Conference on Environmental Science and Information Application Technology (ESIAT 2014), November 7-8, 2014, Hong Kong. (2015) - Unknown
No abstract available